Edge effects on insect-plant food webs: Assessing the influence of geographical orientation and microclimatic conditions - Bernaschini, Maria Laura (2020)
1. Geographical orientation affects the magnitude of microclimatic edge effects, mainly by altering the exposure to solar radiation. There is considerable evidence about the influence of microclimatic edge effects on organisms at the population level, but little is known about effects at the community level, and variations with edge geographical orientation have barely been addressed. This study tested the influence of microclimatic conditions at the forest interior and edges with different geographical orientation on plant-leafminer-parasitoid food webs in the fragmented Chaco Serrano forest located in Central Argentina. 2. We measured microclimatic variables in three locations: interior, north and south-facing edges of six forest fragments. In each location, we assessed plant resource availability and collected mined leaves to study plant-leafminer-parasitoid communities by rearing leafminer and parasitoid adults. 3. Our results revealed changes in the specific composition of plant, leafminer and parasitoid communities among locations, but failed to detect location influences on most variables linked to abundance (except for leafminers), richness or food web structure. Leafminer abundance was negatively related to temperature, whereas their richness was related, also negatively, to moisture. Instead, parasitoids were favored by higher temperatures and light levels, stronger winds and lower humidity. 4. The results of this study indicate that the effects of microclimatic conditions may depend on the trophic level considered. Moreover, our findings suggest that possible trade-offs between direct and indirect effects (such as plant quality, floral resources, etc) of microclimatic conditions could influence plant and insect responses to location.